2019
DOI: 10.1136/annrheumdis-2019-215164
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of peficitinib (ASP015K) in patients with rheumatoid arthritis and an inadequate response to methotrexate: results of a phase III randomised, double-blind, placebo-controlled trial (RAJ4) in Japan

Abstract: ObjectiveTo evaluate the efficacy and safety of the oral Janus kinase (JAK) inhibitor peficitinib versus placebo in Japanese patients with rheumatoid arthritis (RA).MethodsIn this multicentre, double-blind, parallel-group, placebo-controlled phase III study, patients with RA and inadequate response to methotrexate (MTX) were randomised 1:1:1 to placebo, peficitinib 100 mg once daily or peficitinib 150 mg once daily with MTX for 52 weeks. Based on baseline randomisation, at week 12, non-responders receiving pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 39 publications
6
131
2
Order By: Relevance
“…As peficitinib is intended for long-term use in patients with RA, longer-term pharmacokinetic, pharmacodynamic, and safety assessments are required in male and female patients taking concomitant medications. Short-and longer-term safety were investigated in the phase 2b and phase 3 studies performed with male and female RA patients, even though some concomitant medication use was not allowed [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As peficitinib is intended for long-term use in patients with RA, longer-term pharmacokinetic, pharmacodynamic, and safety assessments are required in male and female patients taking concomitant medications. Short-and longer-term safety were investigated in the phase 2b and phase 3 studies performed with male and female RA patients, even though some concomitant medication use was not allowed [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Following a successful clinical development program [12][13][14], peficitinib has recently received its first global approval in Japan as a once-daily treatment for patients with RA who have an inadequate response to conventional therapies [15,16]. However, as the previous pharmacokinetic/ pharmacodynamic studies were performed in mainly Caucasian subjects, and as these parameters can vary in different ethnicities [17], this study was performed to investigate the pharmacokinetics, pharmacodynamics, and safety and tolerability of peficitinib in Japanese subjects, as well as to compare the pharmacokinetic and pharmacodynamic profiles for Japanese and Caucasian subjects.…”
Section: Sample Sizementioning
confidence: 99%
“…The present study compared the pharmacokinetics and safety of a single oral dose of peficitinib in subjects with and without impaired renal function. A single 150 mg oral dose was selected as the 'usual' clinical dose based on the daily dose of peficitinib in Phase III studies in Japanese patients with RA (100 mg and 150 mg) [11,12,20]. In this study, we evaluated the pharmacokinetic profile of a single oral dose of peficitinib 150 mg in subjects with normal renal function and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Peficitinib (ASP015K) is a novel, pan-JAK inhibitor that inhibits JAK1, JAK2, JAK3, and TYK2 [9]. In clinical studies, peficitinib has been shown to be efficacious as once-daily therapy for moderate-to-severe RA, with a rate of treatment-emergent adverse events (TEAEs) comparable with placebo at doses up to 150 mg [10][11][12]. This formed the basis for the recent approval of peficitinib (50 mg and 100 mg tablets) in Japan; the usual clinical dosage for adult patients with RA is 150 mg per day, which can be reduced to 100 mg per day depending on the patient's condition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-IFN-c and anti-TNF-a antibodies showed similar efficacy in patients with active RA [3], whereas a more recent phase 2 clinical trial investigating the use of fontolizumab, a humanized anti-IFN-c monoclonal antibody, for RA was terminated in 2006 because it did not meet the primary endpoint ACR50 at week 14 [4]. Janus kinase (JAK) inhibitors target multiple cytokines including IFN-c and interleukin (IL)-6 and exhibit a beneficial treatment effect in patients with RA and inadequate response to conventional synthetic or biologic disease-modifying anti-rheumatic drugs (DMARDs) [5][6][7]. Even for patients refractory to anti-IL-6 therapy, the treatment effect of JAK inhibitors is promising [8,9], putatively indicating roles of multiple cytokines in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%